The Hand of God or the Work of the Devil? Spiritual Appraisals and Psychological Adjustment After the 2016 U.S. Presidential Election. Issue 1 (11th July 2019) - Wong, Serena; Waite, Tabitha; Wasson, Rachel S.; Artschwager, Augustus; Pargament, Kenneth I.; O'Brien, William H.
Abstract: To what extent do people perceive the election of President Trump as the work of evil forces, a violation of the sacred, or the will of God? Demonization and desecration are negative spiritual appraisals associated with psychological maladjustment across political and relational contexts. Sanctification refers to the imbuing of persons, objects, or events with sacred qualities or as manifestations of a higher power. The authors examined the prevalence and role of spiritual appraisals related to the 2016 U.S. presidential election result on psychological adjustment and behaviors using a cross‐sectional online sample of 252 American voters. Approximately one‐fifth of participants sanctified the election of President Trump to some degree. Conversely, approximately one‐third of participants endorsed some level of negative spiritual appraisals. Desecration and demonization also uniquely predicted maladjustment. Moreover, the interactive effect between vote and negative spiritual appraisals accounted for unique variance in maladjustment. At higher levels of demonization and desecration, those who voted for President Trump reported greater difficulties with emotion regulation than those who voted against President Trump. Negative spiritual appraisals also moderated the relations between vote and thought suppression, in addition to vote and information seeking behavior. For the small fraction of Trump voters with negative spiritual appraisals, their efforts to suppress misgivings, struggle with emotions, and seek information may be understood as attempts to reduce cognitive dissonance.